Toward interfacing organic semiconductors with ferromagnetic transition metal substrates: enhanced stability via carboxylate anchoring. Issue 63 (15th July 2016) - Han, R.; Blobner, F.; Bauer, J.; Duncan, D. A.; Barth, J. V.; Feulner, P.; Allegretti, F.
Abstract : The controlled growth of chemically and structurally well-defined as well as thermally stable carboxylate-anchored self-assembled monolayers on ferromagnetic 3d transition metal substrates provides promising model systems for advanced studies of spin-dependent electron transport. Abstract : We demonstrate that chemically well-defined aromatic self-assembled monolayers (SAMs) bonded via a carboxylate head group to surfaces of ferromagnetic (FM = Co, Ni, Fe) transition metals can be prepared at ambient temperature in ultra-high vacuum and are thermally stable up to 350–400 K (depending on the metal). The much superior stability over thiolate-bonded SAMs, which readily decompose above 200 K, and the excellent electronic communication guaranteed by the carboxylate bonding render benzoate/FM-metal interfaces promising candidates for application in spintronics.